Future orientation and self-efficacy: How does its impact on entrepreneurial readiness? - Rahmawati, Listiana; Tentama, Fatwa (Universitas Mercu Buana Yogyakarta, 2024)
One of the impacts of the COVID-19 pandemic is that many micro businesses have gone bankrupt or even closed their businesses. Micro businesses require entrepreneurial readiness to restart and manage their enterprises effectively. This study aimed to analyze the influence of the model of future orientation and self-efficacy on entrepreneurial readiness in micro-enterprises located in Sleman Regency. This research employed a quantitative approach, focusing on micro-enterprises in Sleman Regency that are members of the 'Sobat PLUT' group in 2022. The sample consisted of 85 under 40 micro-entrepreneurs whose businesses experienced losses due to the COVID-19 pandemic. The study utilized purposive sampling as its sampling technique. Data collection involved three scales: the entrepreneurial readiness scale, the future orientation scale, and the self-efficacy scale. Data analysis was conducted by testing both the outer and inner models. The analysis technique employed the Structural Equation Model (SEM) using the Smart Partial Least Square (Smart-PLS) 3.2.8 program. The results of this study indicate the formation of a model of entrepreneurial readiness, focusing on future orientation and self-efficacy. Future orientation has a significant favorable influence on the entrepreneurial readiness of micro-entrepreneurs and a very significant positive effect of self-efficacy on their entrepreneurial readiness. The theoretical model developed in this research is a fit model that can serve as a reliable model reference for understanding entrepreneurial readiness.